Towards Inclusive and Quality Education: A Critical Evaluation of the School Operational Assistance Policy in North Bolaang Mongondow - Ismail, Edhi; Aneta, Asna; Abdussamad, Zuchri; Abdussamad, Juriko; Aneta, Yanti (Journal Public Policy, 2026)
This study critically evaluates the School Operational Assistance (BOS) policy in enhancing inclusive and quality education in North Bolaang Mongondow Regency. The objective is to assess the policy’s effectiveness in improving educational access, quality, and equity, particularly in bridging gaps between urban and rural schools. Employing a qualitative descriptive method, the research analyzes participation and retention rates in BOS-funded schools, as well as compares access to education before and after the program’s implementation. Findings show that the BOS program significantly contributes to increasing student enrollment, enhancing school performance, and reducing educational disparities. However, challenges persist, including delayed fund disbursements, burdensome administrative processes, and weak monitoring and accountability mechanisms, which hinder optimal utilization of resources at the school level. Despite these limitations, the BOS policy remains a vital tool for promoting educational equity. The study recommends policy refinement through strengthened school management capacity, strategic planning, and evidence-based monitoring and evaluation systems. The proposed roadmap—comprising analysis, corrective action, and continuous learning—is essential for sustainable policy improvement. This research highlights the need for further longitudinal studies with mixed methods to evaluate long-term impacts and support the development of more responsive education policies. Ultimately, improved BOS governance is key to fostering inclusive, equitable, and high-quality education across the region.